Implementasi Standar Pelayanan Program SAKTI di Kelurahan Bujel Kota Kediri - Fendy Artha Prissando; Imam Fachruddin; Djoko Susanto; Mashuri Mashuri (FISIP UWP, 2022)
This study aims to describe and analyze the implementation of e-government services with the SAKTI program in Bujel Village in realizing excellent public services. This research focuses on Public Service Standards according to the Decree of the Minister of Administrative Reform No. 63 of 2003 which includes Service Procedures, Completion Time, Service Fees, Service Products, Facilities and Infrastructure, Competence of Service Providers. The research approach chosen in this research is descriptive qualitative research. The determination of the research location was based on the consideration that Bujel Village, Kediri City, was an active village in implementing e-Government compared to other villages in Bujel District, in addition to preliminary observations it was found that the SAKTI service experienced problems from the Dispenduk server so that various requests for certificate services could usually be made. online, while it can only be done by visiting the kelurahan office directly. The researchers determined the data sources in this study using a purposive sampling technique. The data collection technique used in this research is the method of interview, observation, and documentation. The data analysis technique used in this study is the data analysis technique of the Miles (2014) model which is also known as the interactive data analysis technique. Based on the results and discussion, the implementation of e-government services with the SAKTI program in the Bujel Village has been going well although there are still obstacles from the lack of socialization from the government, the SAKTI server error that makes the service process take a long time and the existing facilities and infrastructure at the Bujel Village Office be less than optimal, but it does not affect the quality of services provided. Services through the SAKTI program can still be done well. Keywords: Public Service, e-Government, Program Implementation